How to make money with social media : an insider's guide on using new and emerging media to grow your business - Turner, Jamie , 1961-; Shah, Reshma , 1964- (Upper Saddle River, New Jersey : FT Press, 2011)
This guide is written by experts who've developed money-making marketing campaigns for many of the world's largest companies. This book shows how to avoid crucial pitfalls that other companies have encounter, how to make the most of limited resources, and how to strengthen your brand instead of placing it at risk.--[book jacket]
1. The social media landscape -- 2. How to set yourself up for social media success -- 3. Social media platforms -- 4. Social media integration -- 5. How to measure social media -- 6. Conclusion
Includes index
Keywords: Internet marketing; Online social networks -- Economic aspects; Social media -- Economic aspects